Heat-related illness among workers in British Columbia, Canada: Extreme hot weather in 2021 compared to 2001-2020 - Xiaocong Guo; Kate R Weinberger; Lillian Tamburic; Cheryl E Peters; Christopher B McLeod (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
OBJECTIVES: British Columbia (BC), Canada, experienced an unprecedented summer with record-breaking high temperatures in 2021. Yet the health impact has not been examined in occupational settings. This study aimed to characterize occupational heat-related illness (HRI) among BC workers estimated by incidence rates and associations between heatwaves and HRI, compare risks from 2021 and prior summers of 2001-2020, and assess differential impacts on worker groups by demographics and occupations. METHODS: We identified HRI from workers' compensation claims that occurred between June and August from 2001-2021 in BC. Incidence rates were calculated using working population estimates from Statistics Canada's Labour Force Survey. A time-stratified case-crossover design with conditional Poisson regression was used to examine the impact of heatwaves on occupational HRI. All analyses were stratified by year (2021 versus 2001-2020), age, sex, and occupation. RESULTS: Of the 521 claims identified, 107 (21%) occurred in 2021. Incidence rates for 2021 and prior summers were 3.97 [95% confidence interval (CI) 3.26-4.80] and 0.93 (95% CI 0.85-1.03) claims per 100 000 workers, respectively. This difference represents a 327% increase. Rates were higher in health occupations in 2021 versus 2001-2020. During 2001-2021, the risk of HRI during heatwave days was 4.33 (95% CI 2.98-6.27) times that during non-heatwave days, and the risk was higher among middle-aged workers and workers in trades, transport, and equipment operations. The 2021 heatwaves had greater impact on younger and female workers than those from prior summers. CONCLUSIONS: Heat is a crucial workplace hazard. Prevention strategies should prioritize at-risk workers and not be limited to heatwaves.